THE COMPARATIVE MOLECULAR GENETICAL STUDY OF ASIAN POPULATIONS OF DROSOPHILA MERCATORUM (DIPTERA; DROSOPHILIDAE) ON THE COI GENE AND ITS1-ITS2 rRNA GENES FRAGMENTS - A. V. Ivannikov; O. V. Vaulin; Yu. A. Koromyslov; I. K. Zakharov (Вавиловский журнал генетики и селекции)
The Drosophila mercatorum species of neotropical origin is composed of two subspecies: mercatorum and pararepleta. The D. m. mercatorum subspecies is synanthropic. It appeared in Eurasia in the middle of the 20th century and dispersed widely. The objects of the study were: D. m. mercatorum specimens from Asian populations, D. mercatorum laboratory stock 2328 (showing some morphological differences), D. busckii and D. virilis specimens, and the sequence of the COI gene of D. mercatorum, NCBI accession number DQ471607. The variability of standard DNA sequences used for species identification (COI fragment and ITS1-ITS2 fragment of rRNA genes) was investigated in these specimens. Asian specimens of D. m. mercatorum had identical COI sequences to each other but differed from sequences of stock 2328 and NCBI sequence. The Asian specimens and stock 2328 were identical in ITS1-ITS2 sequences. The low degree of nucleotide differences between the Asian specimens and morphological distinct stock 2328 in the nucleotide sequences of the COI gene fragment and absence of differences in ITS1-ITS2 of rRNA genes indicate that divergence between these two groups is within the intraspecies variation.